Estimation of Nuclear DNA Content by Flow Cytometry in Saraca asoca (Roxb.) de Wilde - Arathi, S.; Muthu Bhavani, M.; Warrier, Rekha R. (Indian Forester, 2023)
The article details the procedures and techniques for the estimation of absolute DNA amounts in Saraca asoca, a species described ‘Vulnerable’ by the IUCN using flow cytometry, with special emphasis on the preparation of nuclei suspensions, DNA staining and the use of reference standards. Using this technique, the genome size of Saraca asoca is estimated to be ~1430Mb. This is the first report on the genome size of S.asoca.